1996
DOI: 10.1093/oxfordjournals.eurheartj.a014760
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations of ultrasonic integrated backscatter in normal and myopathicleft ventricles. A new multi-view approach

Abstract: The purpose of the present study was to determine whether the cyclic variation of integrated backscatter is measurable and quantifiable in all left ventricular walls and whether the information obtained using both parasternal and apical transducer positions can be used to identify changes in myocardial structure and contractility. The cyclic variation of integrated backscatter was measured from the parasternal long-axis, apical four-chamber and two-chamber views in 26 patients with idiopathic dilated cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…CV of IBS is dependent on the angle between fiber orientation and ultrasonic beam, called anisotropy. 17 We measured CV only in anterior and posterior (control) wall in the short-axis view, in which myocardial fiber is oriented nearly perpendicular to the ultrasound beam, to avoid problems with anisotropy as possible. It is unclear whether the results in the present study could be applied to inferior or lateral wall infarction because of anisotropy.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CV of IBS is dependent on the angle between fiber orientation and ultrasonic beam, called anisotropy. 17 We measured CV only in anterior and posterior (control) wall in the short-axis view, in which myocardial fiber is oriented nearly perpendicular to the ultrasound beam, to avoid problems with anisotropy as possible. It is unclear whether the results in the present study could be applied to inferior or lateral wall infarction because of anisotropy.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Measurement of CV on apical views might be also useful for detecting coronary reperfusion to reduce anisotropy. 17 The quality of echocardiographic images also could affect analysis of IBS, and approximately 10% of the study patients were excluded because of inadequate echocardiographic images. This method might also not be inapplicable for the patients having prior myocardial infarction, bundle branch block, paced rhythm, or cardiomyopathy.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Recently, the analysis of IB and strain rate imaging have been used to detect myocardial structural and functional abnormalities in various cardiac conditions, and it has been shown that IB analysis has a higher ability to assess myocardial fibrosis in comparison with strain rate imaging [13]. Previous studies have demonstrated that the analysis of IB has the potential to assess myocardial interstitial fibrosis and intrinsic myocardial contractility in DCM [9,10]. These clinical observations have revealed an increased calibrated IB and a reduced CV-IB in patients with DCM, and it has been reported that both parameters correlate with a histologic estimate of myocardial fibrosis in the biopsy specimen of DCM patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated ultrasonic tissue characterization in patients with DCM, and have shown that the analysis of IB has the potential to assess the myocardial interstitial fibrosis and intrinsic myocardial contractility in DCM [9,10]. We have thus hypothesized that a close relationship should exist between the activity of angiogenic factors and alterations in myocardial texture in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic variation of integrated backscatter (CV-IBS) decreases with myocardial cell injury, a property that assists in detecting subclinical myocardial damage. [15][16][17][18][19][20] In the current study, we measured the acoustic properties of the myocardium in patients with normal left ventricular contractile function who were receiving DXR to determine the feasibility of using CV-IBS for detecting an early phase of DXR-induced myocardial damage.…”
mentioning
confidence: 99%